Cognitive and physiological effects of an acute physical activity intervention in elementary school children - Jäger, Katja; Schmidt, Mirko; Conzelmann, Achim; Roebers, Claudia M. (Frontiers in Psychology, 2014)
The aim of the present study was to investigate the effects of an acute physical activity intervention including cognitive engagement on executive functions and on cortisol level in young elementary school children. Half of the 104 participating children (6 to 8 years old) attended a 20-minute sport sequence, which included cognitively engaging and playful forms of physical activity. The other half was assigned to a resting control condition. Individual differences in children`s updating, inhibition, and shifting performance as well as salivary cortisol were assessed before (pre-test), immediately after (post-test), and 40 minutes after (follow-up) the intervention or control condition respectively. Results revealed a significantly stronger improvement in inhibition in the experimental group compared to the control group, while it appeared that acute physical activity had no specific effect on updating and shifting. The intervention effect on inhibition levelled out 40 minutes after physical activity. Salivary cortisol increased significantly more in the experimental compared to the control group between post-test and follow-up and results support partly the assumed inverted U-shaped relationship between cortisol level and cognitive performance. In conclusion, results indicate that acute physical activity including cognitive engagement may have immediate positive effects on inhibition, but not necessarily on updating and shifting in elementary school children. This positive effect may partly be explained trough cortisol elevation after acute physical activity.